Teaching kinematics and dynamics of multibody mechanical systems using the object oriented language modelica - Seabra, Eurico (2009)
A new modeling language, called Modelica, for physical modeling is being developed in an international effort. The main objective is to make it easy to exchange models and model libraries for different domains, such as, mechanical, pneumatics, electrical, hydraulics, and others. The design approach builds on non-causal modeling with true ordinary differential and algebraic equations and the use of object-oriented constructs stemming from modern software development, (hierarchy, encapsulation) to facilitate reuse of models and model parts. This paper gives an overview of the use of the object oriented language Modelica with the mechanical Multibody Library to model and simulate three-dimensional mechanical systems.